Application of augmented reality in education - Raden Mochamad Arivya Trikotama; Mohammad Nazwan Nurrohman; Debora Keisha Hutajulu (Himpunan Pengembang Kurikulum Indonesia, 2024)
The development of character and human resource quality can be improved by sustainable educational innovation in teaching methods and media, so educators must create an attractive and informative learning environment. One of these innovations is using augmented reality (AR) in education, which can produce generations of creative, innovative, and competitive individuals. This study uses the literature review (literature review) analysis method by analyzing the urgency of applying augmented reality (AR) in education in the era of society 5.0. This study aims to examine the development of AR technology in Indonesia's education world and its impact on improving the quality of education in Indonesia both now and in the future. The study results show that AR has the potential to improve the quality of education in Indonesia. AR can increase students' motivation and interest in learning, improve students' understanding of learning concepts, and make the learning process more interactive and engaging. In addition, AR can help prepare young people for a dynamic future. Abstrak Pengembangan karakter dan peningkatan kualitas sumber daya manusia dapat ditingkatkan dengan inovasi pendidikan yang berkelanjutan dalam metode dan media pembelajaran, maka penting bagi pendidik untuk menciptakan lingkungan belajar yang menarik dan informatif. Salah satu inovasi tersebut adalah dengan menggunakan augmented reality (AR) ke dalam pendidikan yang dapat mampu menghasilkan generasi individu yang kreatif, inovatif dan kompetitif. Penelitian ini bertujuan untuk mengkaji perkembangan teknologi AR dalam dunia pendidikan di Indonesia dan dampak yang dihasilkan dari penggunaan AR dalam meningkatkan kualitas pendidikan di Indonesia baik sekarang maupun di masa depan. Penelitian ini menggunakan metode analisis kajian pustaka (literatur review) dengan menganalisis tentang urgensi penerapan augmented reality (AR) pada pendidikan di era society 5.0. Hasil penelitian menunjukkan bahwa AR memiliki potensi untuk meningkatkan kualitas pendidikan di Indonesia. AR dapat meningkatkan motivasi dan minat peserta didik untuk belajar, meningkatkan pemahaman peserta didik tentang konsep pembelajaran, dan membuat proses pembelajaran lebih interaktif dan menarik. Selain itu, AR dapat membantu mempersiapkan generasi muda untuk masa depan yang dinamis. Kata Kunci: pendidikan 5.0; realitas tertambah; teknologi pendidikan